Depression, anxiety, and help-seeking among Slovenian postsecondary students during the COVID-19 pandemic - Selak, Špela; Lebar, Maša; Žvelc, Gregor; Gabrovec, Branko; Šorgo, Andrej; Cesar, Katarina; Crnkovič, Nuša (Frontiers in Psychology, 2024)
Introduction: The COVID-19 pandemic has faced students with many challenges, contributing to their mental distress. This article explores the role of demographic characteristics, psychological status, year of study, and social support during the COVID-19 pandemic in explaining Slovenian university students' mental health problems and help-seeking behavior. Methods: In February and March 2021, data were collected on 5,234 full-time Slovenian postsecondary students who were enrolled in public and concessionary independent higher education institutions. Participants completed a questionnaire, which included The Patient Health Questionnaire (PHQ-9), General Anxiety Disorder questionnaire (GAD-7), Oslo Social Support Scale (OSSS-3), and items measuring psychological status, help-seeking behavior and demographics. Data were analyzed using multiple linear regression and hypothesis testing for differences. Results: Factors, such as gender, age, psychological status and social support, contributed to experiencing anxiety and depression among Slovenian students during the COVID-19 pandemic, with year of study additionally contributing to experiencing depression. Similarly, gender, age, psychological status and social support contributed to help-seeking behavior. Higher levels of depression and anxiety were reported by female students, students with prior mental disorders, and students with lower social support levels. Female students and students with lower social support levels reported more frequent help-seeking behaviors. Conclusions: The results provide insight into the mental state of the Slovenian student population in the context of imposed public health measures at the end of the second COVID-19 wave in Slovenia. The findings can help identify vulnerable groups within the student population to whom we must be particularly attentive in times of crisis.